NADPH Oxidase-Dependent Formation of Reactive Oxygen Species Contributes to Transforming Growth Factor 13 I-Induced EpitheliaI-Mesenchymal Transition in Rat Peritoneal Mesothelial Cells, and the Role of Astragalus Intervention - 刘小贤 周红娟 蔡龙 张雯 马纪林 陶筱娟 于健宁 (中国结合医学杂志：英文版, 2014)
Objective： To investigate the role of nicatinamide-adenine dinucleotide phosphate （NADPH） oxidase- dependent formation of reactive oxygen species （ROS） in the transforming growth factor β1 （TGF-β 1）-induced epithelial-mesenchymal transition （EMT） in rat peritoneal mesothelial ceils （RPMCs）, and the effect of Astragalus injection （AGI） intervention. Methods： Primary RPMCs were cultured to the second generation in vitro. After synchronization for 24 h, the calls were randomly assigned to the following groups： control （Group A）, AGI （2 g/mL; Group B）, TGF- β1 （10 ng/mL; Group C）, TGF- β1 （10 ng/mL） ＋ AGI （2 g/mL; Group D; pretreated for 1 h with AGI before TGF-β 1 stimulation）. Reverse transcription-polymerase chain reaction （RT-PCR） and Westem blot analysis were employed to evaluate the mRNA and protein expression of the NADPH oxidase subunit p67phox, e-smooth muscle actin （α -SMA） and E-cadherin. The dichlorofluorescain-sensitive cellular ROS levels were measured by a fluorometric assay and confocal microscopy. Results： TGF- β1 significantly induced NADPH oxidase subunit p67phox mRNA and protein expression in RPMCs, as well as inducing the production of intracellular ROS. AGI inhibited this TGF- β1-induced up-regulation by 39.3% and 47.8%, respectively （P〈0.05）, as well as inhibiting the TGF- β 1- induced ROS generation by 56.3% （P〈0.05）. TGF- β 1 also induced α-SMA mRNA and protein expression, and down-regulated E-cadhedn mRNA and protein expression （P〈0.05）. This effect was suppressed by AGI （P〈0.05）. Conclusions： NADPH oxidase-dependent formation of ROS may mediate the TGF- β1-dependent EMT in RPMCs. AGI could inhib/t this process, providing a theoretical basis for AGI in the prevention of peritoneal fibrosis.